Doubts regarding the negotiation of equality plans: the court’s response - Ramo Herrando, María José (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract. They are not few the interpretative problems that arise when addressing the collective bargaining of an equality plan. The first doubts may appear when the negotiating table is formed, especially when there are work centers with legal representation of the workers and others without this representation; then, the principle of correspondence may be affected. It also raises questions the scope that must be given to the legal requirement that it has to be at the negotiating table where the diagnosis of equality is drawn up, or if the obligation to negotiate the plan requires reaching an agreement or is a mere obligation of means, or the consequences that may result from breaching the plan measures or the information commitments during the plan follow-up phase.These and other interpretative issues are very important since they can lead to the declaration of nullity of the equality plan and even to sentences of compensation amounts for the infringement of the constitutional right of freedom of association and pecuniary constraints. The courts have been answering these questions, thus providing greater legal security to the negotiation process of the equality plans.